Leishmania infantum Exoproducts Inhibit Human Invariant NKT Cell Expansion and Activation - Belo, Renata; Santarém, Nuno; Pereira, Cátia; Pérez-Cabezas, Begoña; Macedo, Fátima; Leite-de-Moraes, Maria; Cordeiro-da-Silva, Anabela (Frontiers in Immunology, 2017)
Leishmania infantum is one of the major parasite species associated with visceral leishmaniasis, a severe form of the disease that can become lethal if untreated. This obligate intracellular parasite has developed diverse strategies to escape the host immune response, such as exoproducts (Exo) carrying a wide range of molecules, including parasite virulence factors, which are potentially implicated in early stages of infection. Herein, we report that L. infantum Exo and its two fractions composed of extracellular vesicles (EV) and vesicle-depleted-exoproducts (VDE) inhibit human peripheral blood invariant Natural Killer T (iNKT) cell expansion in response to their specific ligand, the glycolipid α-GalactosylCeramide (α-GalCer), as well as their capacity to promptly produce IL-4 and IFNγ, Using plate-bound CD1d and α-GalCer, we found that Exo, EV and VDE fractions reduced iNKT cell activation in a dose-dependent manner, suggesting that they prevented α-GalCer presentation by CD1d molecules. This direct effect on CD1d was confirmed by the observation that CD1d:α-GalCer complex formation was impaired in the presence of Exo, EV and VDE fractions. Furthermore, lipid extracts from the three compounds mimicked the inhibition of iNKT cell activation. These lipid components of L. infantum exoproducts, including EV and VDE fractions, might compete for CD1 binding sites, thus blocking iNKT cell activation. Overall, our results provide evidence for a novel strategy through which L. infantum can evade immune responses of mammalian host cells by preventing iNKT lymphocytes from recognizing glycolipids in a TCR-dependent manner.